Examining The Challenges In Production Encountered Bycoir Enterprises In Tamil Nadu To Promote Economic Growth And Sustainability (International Journal of Environmental Sciences, 2025)
The article reveals the analysis of production challenges encountered by small coir units, focusing on economic growth and sustainability. The coir industry in India is characterized as an agro-based, village, and cottage industry. Despite its significant contributions to employment and the income of individuals, as well as the overall economy of the country in various ways, the coir sector does not receive the necessary support from the government, banks, financial institutions, and other lending bodies. This lack of support hinders the provision of quality goods and services, the ability to compete effectively, the creation of demand, and the attraction of customers in both national and international markets. Although the coir sector holds considerable potential in India, it is confronted with numerous challenges. The study indicated that, based on mean scores, inadequate financing was the most pressing issue, achieving a mean score of 70.74, which was higher than any other identified problems.